A STATE-OF-ART REVIEW ON EFFECT OF VARIOUS PILE ARRANGEMENT CONFIGURATION ON PILE RAFT FOUNDATION - Dr. Anuj K. Chandiwala; Dr. Mital J. Dholawala; Dr. Soumita D. Bid; Dr. Tandra Banerjee; Dr. Digant Pastagia (Utilitas Mathematica, 2025)
Pile raft foundations (PRFs) synergize the load-bearing capacities of piles and rafts, making them an optimal solution for supporting heavy structures on soft or weak soils. By distributing loads through both components, PRFs mitigate settlement and enhance foundation efficiency, offering a cost-effective alternative to conventional pile or raft-only systems. This research conducts a comprehensive review of the effects of different pile arrangement configurations on PRF performance. It integrates findings from experimental studies, numerical simulations, and field investigations to assess key aspects such as load-sharing mechanisms, settlement characteristics, and stress distribution. The study highlights the critical influence of pile spacing, arrangement patterns (e.g., uniform, clustered, or concentric), and pile-raft interaction on foundation behavior. Specifically, it identifies how these factors affect load distribution between the raft and piles, mitigate differential settlement, and optimize stress transfer to the subsoil. By synthesizing current knowledge, the review provides valuable insights into designing PRFs for diverse geotechnical conditions. It emphasizes site-specific optimization, leveraging advanced numerical modeling, and understanding soil-structure interaction to achieve efficient and reliable designs. This work aims to guide engineers and researchers in refining PRF configurations, balancing cost-effectiveness with safety and performance for complex foundation challenges.